Pembentukan Identitas Religius Anak melalui Kegiatan Lomba Islami di Desa Ujung Negeri Kahan: Indonesia - Fauziah Nasution; Chadiza Auliana Utami; Annisa Hasanah Nasution; Annisa Wibowo; Desy Kartika Dewi (Jurnal Pemberdayaan: Publikasi Hasil Pengabdian Kepada Masyarakat, 2026)
Islamic competitions in Ujung Negeri Kahan Village serve as an important social space for the formation of children's religious identity through participatory experiences and community interactions. This study aims to describe the role of Islamic competitions in shaping children's religious identity within the context of village life. The study used a qualitative approach using observation, in-depth interviews, and documentation techniques with child participants, their parents, and activity facilitators. The results indicate that Islamic competitions serve as a medium for internalizing religious values, strengthening self-confidence, discipline, and pride in religious identity. Community support provides social reinforcement that associates children's religious practices with positive experiences. This activity demonstrates that community-based religious education can be an effective cultural mechanism for instilling religious character in children in a contextual and sustainable manner.